Development Of Augmented Reality (Ar)-Based Flashcard Learning Media For Mail Handling Material In Phase F Office Management At SMKN 44 Jakarta - Rena Maretha Sari; Dewi Nurmalasari; Bayu Suhendry (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to develop Augmented Reality (AR)-based Flashcard learning media for Mail Handling material in Phase F of the Office Management Skills Program at SMK Negeri 44 Jakarta. This research was motivated by the use of conventional learning media that are less effective in visualizing mail handling procedures, causing students to experience difficulties in understanding the material and participate actively in learning. Therefore, innovative and interactive technology-based learning media are needed. This study employed the Research and Development (R&D) method using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through validation by material, media, and instructional design experts, student response questionnaires, and pre-tests and post-tests. Data were analyzed using quantitative and qualitative descriptive analysis. The results showed that material expert validation obtained 98%, categorized as very feasible; media expert validation obtained 79%, categorized as feasible; and instructional design expert validation obtained 84%, categorized as very feasible, with an average of 87%, categorized as very feasible. The practicality test based on student responses obtained 91% in the one-to-one test, 96% in the small-group test, and 95% in the large-group test, all categorized as very practical. The N-Gain effectiveness test obtained a score of 0.77, categorized as high. Thus, the AR-based Flashcard learning media is feasible, practical, and effective as an alternative learning medium for Mail Handling material in Phase F.